Time-dependence of chloride diffusion for concrete containing metakaolin. (September 2016) - Al-alaily, Hossam S.; Hassan, Assem A.A.
Abstract: Chloride diffusion coefficient depends on many variables including concrete quality, environmental conditions, and time. In this investigation, the concrete quality and time were studied while maintaining the environmental conditions constant. Fifty-three concrete mixtures were tested based on a refined statistical analysis. Enhanced response surface method (RSM) was used to present the most significant factors affecting the chloride diffusion at different ages. The tested mixtures contained various water-to-binder (W/B) (ratios 0.3–0.5), metakaolin (MK) replacement (0–25%), and total binder content (350–600 kg/m 3 ). Bulk diffusion test was adopted for two years to determine the time-dependent coefficient m of chloride diffusion for all mixtures based on the error function solution to Fick's law. This coefficient was calculated based on two different bulk diffusion test methods: total and average methods. Design charts were developed to facilitate the optimization of mixture proportions for designers/engineers. The investigation also included some experimental relationships between the rapid chloride permeability test (RCPT), chloride diffusion coefficient, and compressive strength results. The results showed that the values of the chloride diffusion indicated a general reduction from 28 days to 760 days of testing. As the percentage of MK or binder content increased or as the W/B ratio decrease, the chloride diffusion reduction coefficients, m total and m avr, were found to increase. Based on the analysis of variance (ANOVA) from the statistical model, MK was found to be the most significant factor affecting the chloride diffusion at late ages (360 and 720 days), while the W/B ratio was the most significant factor affecting early ages of chloride diffusion (28 and 90 days). The developed models and design charts in this paper can be of special interest to designers/engineers by aiding prediction of service life of concrete containing MK. Highlights: The time-dependent coefficient of chloride diffusion was determined Relationships between RCPT, chloride diffusion, and f′c were obtained Chloride diffusion indicated a general reduction from 28 days to 760 days As the % of MK increased the diffusion reduction coefficients increase As the binder content increased the diffusion reduction coefficients increase